2019
DOI: 10.3748/wjg.v25.i16.1928
|View full text |Cite
|
Sign up to set email alerts
|

Upper gastrointestinal tract involvement of pediatric inflammatory bowel disease: A pathological review

Abstract: Upper gastrointestinal (UGI) tract involvement of inflammatory bowel disease (IBD) is commonly seen in pediatric patients. Upper endoscopy is included in the routine workup of children with suspected IBD to enhance the diagnosis and management of these patients. Currently, childhood IBD is classified into ulcerative colitis (UC), atypical UC, Crohn’s disease (CD) and IBD unclassified. Histologic confirmation of UGI tract involvement, in particular the presence of epithelioid (non-caseating) granulomas, is help… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
44
1
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 43 publications
(78 reference statements)
4
44
1
5
Order By: Relevance
“…6 Studies in pediatric patients who had simultaneous EGD at the time of diagnosis revealed that the prevalence of gastroduodenal involvement of CD is up to 36%-53%. 7,8 According to this result, the surveillance of UGI involvement is conducted as a significant factor in diagnosis, risk and prognostic evaluation of CD. Patient with UGI manifestations have a higher risk of more aggressive stricturing and more penetrating form of the disease, meaning more recurrences, frequent hospitalization, and more surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies in pediatric patients who had simultaneous EGD at the time of diagnosis revealed that the prevalence of gastroduodenal involvement of CD is up to 36%-53%. 7,8 According to this result, the surveillance of UGI involvement is conducted as a significant factor in diagnosis, risk and prognostic evaluation of CD. Patient with UGI manifestations have a higher risk of more aggressive stricturing and more penetrating form of the disease, meaning more recurrences, frequent hospitalization, and more surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic findings of UGI-CD include patchy erythema, mucosal friability, thickened folds, ulcerations, and in severe cases strictures, luminal narrowing, fistula of UGI tract. 7 UGI-CD is relatively rare disease, thus other possible etiologies of gastric outlet obstruction such as peptic ulcer disease, Menetrier disease, collagen vascular disease, various infections like Helicobacter pylori, cytomegalovirus and Mycobacterium tuberculosis, nonsteroidal anti-inflammatory drug use, malignant and infiltrative disease should be ruled out through imaging or upper endoscopy. 10 One-third of patients with isolated UGI-CD do not have small or large intestine disease at the time of diagnosis of CD but develop distal disease over time.…”
Section: Discussionmentioning
confidence: 99%
“…Focal enhanced gastritis (Figure 2A-C) is focal chronic or chronic active inflammation, usually exquisitely focal, and often seemingly centred on a single pit 29,31,32 (Table 2). It has been described in 24%-48% of Crohn's disease patients, and in up to 76% of paediatric patients, but in as few as 10.5% of Table 2.…”
Section: Ibd/inflammatory Bowel Diseasementioning
confidence: 99%
“…It has been described in 24%-48% of Crohn's disease patients, and in up to 76% of paediatric patients, but in as few as 10.5% of Table 2. Gastric lesions in inflammatory bowel disease (IBD); similar lesions appear in both ulcerative colitis and Crohn's disease, but they appear to be more prevalent in Crohn's disease 29,[31][32][33] Schaumann bodies and birefringent crystalline particles can be seen The stomach, in particular the antrum, is affected in systemic disease. 77,78 However, isolated gastric sarcoidosis has also been described 79 adults.…”
Section: Ibd/inflammatory Bowel Diseasementioning
confidence: 99%
See 1 more Smart Citation